Identification of a plant-encoded analog of PKR, the mammalian double-stranded RNA-dependent protein kinase. - Langland, J O (1995)
Plant virus or viroid infection stimulates the phosphorylation of a plant-encoded protein of M(r) 68,000 to 70,000 (now termed pPKR) that is associated with double-stranded RNA-stimulated protein kinase activity. Using various biochemical and immunological comparisons, we have demonstrated that this plant protein is an analog of the mammalian PKR enzymes. pPKR is both cytosolic and ribosome associated, similar to mammalian PKR, and appears to be capable of phosphorylating exogenous histones. Monoclonal anti-serum to the human PKR as well as antiserum to a conserved double-stranded RNA-binding domain present on mammalian PKR demonstrated cross-reactivity with pPKR. Likewise, polyclonal antiserum to the pPKR detected the mouse and human PKR in western blot analysis. Northern blot analysis of a mammalian PKR cDNA detected a specific 2.5-kb transcript present in plant poly (A)+ RNA.